2020
DOI: 10.3390/toxins12060366
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extracts from Cultivated Mushrooms Affect the Production of Fumonisins B and Fusaric Acid by Fusarium verticillioides

Abstract: The maize pathogen Fusarium verticillioides and their mycotoxins cause damage to plants, animals, and human health. This work aimed to evaluate the effect of crude extracts (CEs) from Agaricus subrufescens, Lentinula edodes, and Pleurotus ostreatus fruiting bodies on in vitro production of biomass and mycotoxins by two strains of F. verticillioides. Stipes and pilei were separated before extraction for A. subrufescens and L. edodes. Comparative metabolomics and dereplication of phenolic compounds were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…So, we have proved that our ecological criterium of choosing plants from MCF ecosystems is valid and should be considered for incorporating these plants species in other bioprospecting programs such as drug discovery. In addition, active plant species here described represent opportunities for the isolation and identification of new antifungal compounds against Fusarium spp [36,37] . and bioassay‐guided fractionation approaches should be further considered leading the identification of the bioactive antifungal metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…So, we have proved that our ecological criterium of choosing plants from MCF ecosystems is valid and should be considered for incorporating these plants species in other bioprospecting programs such as drug discovery. In addition, active plant species here described represent opportunities for the isolation and identification of new antifungal compounds against Fusarium spp [36,37] . and bioassay‐guided fractionation approaches should be further considered leading the identification of the bioactive antifungal metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomic studies based on accurate mass spectrometry represent a powerful tool that has been used to gain insights into more efficient management approaches against notorious plant pests and diseases, such as thrips [80], foraging ants [81] and fusarium wilt [82][83][84]. The untargeted metabolomics study we performed reinforces the idea that A. obliqua females can sense fruit chemical quality, as reported for D. melanogaster [79], since we identified biochemical differences between oviposited and non-oviposited sites in "Criollo" mangos (Figures 4b and 5).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that organics extracts from culture filtrates and basidiomes of Agaricus subrufescens (pilei and stipe), Lentinula edodes (pilei), and Pleurotus ostreatus significantly reduced the mycelial growth and production of fusaric acid in Fusarium spp. in vitro (Chen and Huang, 2010;Merel et al, 2020). Interestingly, fusaric acid was recently described as one of the potential virulence factors produced by F. kuroshium (Gutiérrez-Sánchez et al, 2021) and is capable of inducing in vitro foliar damage in avocado, in a similar way to the symptomatology observed in Fusarium dieback.…”
Section: Fungi With Antifungal Activity Against Ambrosia Fungimentioning
confidence: 90%